Practical application of Alzheimer's Disease Neuroimaging Initiative plasma P‐tau181 reference data to support diagnosis of Alzheimer's disease. (8th January 2022) - Hazan, Jemma; Alston, Duncan; Fox, Nick C.; Howard, Robert
Abstract: Objectives: To assess plasma phosphorylated tau181 (p‐tau181) levels in Alzheimer's disease (AD), cognitively impaired non‐AD participants (CI non‐AD) and Control participants in the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset that could potentially act as reference data for clinic diagnoses of AD. Methods: Data from 1558 participants (649 AD participants, 445 CI non‐AD participants and 464 controls) were examined, comparing p‐tau181 levels between Controls, AD and other dementias, stratified by age. Results: There were significant differences in plasma p‐tau181 values between Controls and those with AD at all ages up to 85 years. There were also significant differences between AD and CI non‐AD participants up to the age of 85 years. Conclusions: Plasma P‐tau181 may be a useful tool in the diagnosis of AD in those clinical settings where biomarkers have traditionally been less used. P‐tau181 may be less useful as an aid to diagnosis in the very oldest‐old. Further work is needed to establish the feasibility and utility of this biomarker within dementia diagnosis services not led by Neurologists, such as UK National Health Service Memory Services. Key points: In the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset there were significant differences in plasma p‐tau181 between controls and those with Alzheimer's disease (AD) across all included age ranges, although there was overlap in 95% confidence intervals in the highest age ranges. There were significant differences in plasma p‐tau181 between AD participants and cognitively impaired participants without AD pathology. P‐tau181 may be a useful tool to aid clinicians in the diagnosis of AD in situations where AD biomarkers have not been traditionally used.